T Cell Protein Tyrosine Phosphatase in Osteoimmunology - Wang, Ya-nan; Liu, Shiyue; Jia, Tingting; Feng, Yao; Zhang, Wenjing; Xu, Xin; Zhang, Dongjiao (Frontiers in Immunology, 2021)
Osteoimmunology highlights the two-way communication between bone and immune cells. T cell protein tyrosine phosphatase (TCPTP), also known as protein-tyrosine phosphatase non-receptor 2 (PTPN2), is an intracellular protein tyrosine phosphatase (PTP) essential in regulating immune responses and bone metabolism via dephosphorylating target proteins. Tcptp knockout in systemic or specific immune cells can seriously damage the immune function, resulting in bone metabolism disorders. This review provided fresh insights into the potential role of TCPTP in osteoimmunology. Overall, the regulation of osteoimmunology by TCPTP is extremely complicated. TCPTP negatively regulates macrophages activation and inflammatory factors secretion to inhibit bone resorption. TCPTP regulates T lymphocytes differentiation and T lymphocytes-related cytokines signaling to maintain bone homeostasis. TCPTP is also expected to regulate bone metabolism by targeting B lymphocytes under certain time and conditions. This review offers a comprehensive update on the roles of TCPTP in osteoimmunology, which can be a promising target for the prevention and treatment of inflammatory bone loss.